The Effect of Using Process-Genre Approach on the Tenth Grade Students’ Descriptive Text Writing Achievement at SMA Negeri 1 Pakusari - Akmaliah, Diah; setyono, budi; bindarti, wiwiek eko (EFL Education Journal, 2016)
The aim of this research was to investigate the effect of using processgenre approach on the tenth grade students’ descriptive text writing achievement atSMA Negeri 1 Pakusari. The research design used was quasi-experimental researchwith post-test only control group design. The respondent of the research was chosenby using cluster random sampling. Through a lottery, class X-1 was chosen as anexperimental group and X-2 was chosen as a control group. The data was collectedby writing test and analyzed by using independent sample t-test. The result showedthat the result of t-test analysis was significant. This means that the result of thisresearch proved that the use of process-genre approach significantly affected thetenth grade students’ descriptive text writing achievement at SMA Negeri 1Pakusari.